Matter or illusion of the bioecotoximonitor in aquatic ecotoxicology? - Argota Pérez, George (2024)
Bioassessment in aquatic ecotoxicology faces challenges in achieving precision and depth in environmental analysis, particularly in the identification of contaminants and the assessment of aquatic ecosystem health. In response to this issue, the concept of the "bioecotoximonitor," has emerged as a potential solution for improving environmental evaluation. The objective was to analyze whether bioecotoximonitors represent a solid methodological advancement or if they constitute an illusion that oversimplifies ecological complexity. The methodological perspective of the study focuses on a critical and comparative analysis of the theoretical and practical dimensions of the concept. Considerations include the lack of empirical validation of the bioecotoximonitor and the need to address how multiple environmental factors may influence the accuracy of its application. The study suggests that, while the bioecotoximonitor offers conceptual progress, there are significant gaps in its practical applicability, which could lead to misinterpretations of environmental health. It is concluded that a multidimensional practical methodological development is necessary to ensure that the bioecotoximonitor becomes an effective tool in aquatic ecotoxicology.